Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the function [tex]\( f(x) = 2x - 3 \)[/tex], let's take a detailed step-by-step approach.
Let's break it down as follows:
### Definition
1. The function [tex]\( f(x) \)[/tex] represents a linear relationship between [tex]\( x \)[/tex] and [tex]\( f(x) \)[/tex].
2. In this function, [tex]\( x \)[/tex] is the independent variable, and [tex]\( f(x) \)[/tex] is the dependent variable.
### Calculation Steps
1. Identify the coefficients:
- The coefficient of [tex]\( x \)[/tex] is 2.
- The constant term (y-intercept) is -3.
2. Behavior of the Function:
- This is a linear function with a slope of 2.
- The slope indicates that for every unit increase in [tex]\( x \)[/tex], [tex]\( f(x) \)[/tex] will increase by 2 units.
- The y-intercept is -3, meaning when [tex]\( x = 0 \)[/tex], [tex]\( f(x) \)[/tex] will be -3.
### Important Points on the Graph
1. Intercepts:
- Y-Intercept: When [tex]\( x = 0 \)[/tex], [tex]\( f(0) = 2(0) - 3 = -3 \)[/tex].
- X-Intercept: Set [tex]\( f(x) = 0 \)[/tex] to find where the function crosses the x-axis:
[tex]\[ 0 = 2x - 3 \implies 2x = 3 \implies x = \frac{3}{2} \][/tex]
### Example Values
To illustrate the function with a few example values:
1. When [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2(1) - 3 = 2 - 3 = -1 \][/tex]
2. When [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 2(-1) - 3 = -2 - 3 = -5 \][/tex]
3. When [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2(2) - 3 = 4 - 3 = 1 \][/tex]
### Summary
- The function [tex]\( f(x) = 2x - 3 \)[/tex] is a straight line with a slope of 2.
- It has a y-intercept at (0, -3).
- The x-intercept is at [tex]\(\left(\frac{3}{2}, 0\right)\)[/tex].
By following these steps, we understand the linear function [tex]\( f(x) = 2x - 3 \)[/tex] and its characteristics.
Let's break it down as follows:
### Definition
1. The function [tex]\( f(x) \)[/tex] represents a linear relationship between [tex]\( x \)[/tex] and [tex]\( f(x) \)[/tex].
2. In this function, [tex]\( x \)[/tex] is the independent variable, and [tex]\( f(x) \)[/tex] is the dependent variable.
### Calculation Steps
1. Identify the coefficients:
- The coefficient of [tex]\( x \)[/tex] is 2.
- The constant term (y-intercept) is -3.
2. Behavior of the Function:
- This is a linear function with a slope of 2.
- The slope indicates that for every unit increase in [tex]\( x \)[/tex], [tex]\( f(x) \)[/tex] will increase by 2 units.
- The y-intercept is -3, meaning when [tex]\( x = 0 \)[/tex], [tex]\( f(x) \)[/tex] will be -3.
### Important Points on the Graph
1. Intercepts:
- Y-Intercept: When [tex]\( x = 0 \)[/tex], [tex]\( f(0) = 2(0) - 3 = -3 \)[/tex].
- X-Intercept: Set [tex]\( f(x) = 0 \)[/tex] to find where the function crosses the x-axis:
[tex]\[ 0 = 2x - 3 \implies 2x = 3 \implies x = \frac{3}{2} \][/tex]
### Example Values
To illustrate the function with a few example values:
1. When [tex]\( x = 1 \)[/tex]:
[tex]\[ f(1) = 2(1) - 3 = 2 - 3 = -1 \][/tex]
2. When [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = 2(-1) - 3 = -2 - 3 = -5 \][/tex]
3. When [tex]\( x = 2 \)[/tex]:
[tex]\[ f(2) = 2(2) - 3 = 4 - 3 = 1 \][/tex]
### Summary
- The function [tex]\( f(x) = 2x - 3 \)[/tex] is a straight line with a slope of 2.
- It has a y-intercept at (0, -3).
- The x-intercept is at [tex]\(\left(\frac{3}{2}, 0\right)\)[/tex].
By following these steps, we understand the linear function [tex]\( f(x) = 2x - 3 \)[/tex] and its characteristics.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.